Measurements From Ears With Endolymphatic Hydrops and 2-Hydroxypropyl-Beta-Cyclodextrin Provide Evidence That Loudness Recruitment Can Have a Cochlear Origin - Lefler, Shannon M.; Duncan, Robert K.; Goodman, Shawn S.; Guinan, John J.; Lichtenhan, Jeffery T. (Frontiers in Surgery, 2021)
Background: Loudness recruitment is commonly experienced by patients with putative endolymphatic hydrops. Loudness recruitment is abnormal loudness growth with high-level sounds being perceived as having normal loudness even though hearing thresholds are elevated. The traditional interpretation of recruitment is that cochlear amplification has been reduced. Since the cochlear amplifier acts primarily at low sound levels, an ear with elevated thresholds from reduced cochlear amplification can have normal processing at high sound levels. In humans, recruitment can be studied using perceptual loudness but in animals physiological measurements are used. Recruitment in animal auditory-nerve responses has never been unequivocally demonstrated because the animals used had damage to sensory and neural cells, not solely a reduction of cochlear amplification. Investigators have thus looked for, and found, evidence of recruitment in the auditory central nervous system (CNS). While studies on CNS recruitment are informative, they cannot rule out the traditional interpretation of recruitment originating in the cochlea. Design: We used techniques that could assess hearing function throughout entire frequency- and dynamic-range of hearing. Measurements were made from two animal models: guinea-pig ears with endolymphatic-sac-ablation surgery to produce endolymphatic hydrops, and naïve guinea-pig ears with cochlear perfusions of 13 mM 2-Hydroxypropyl-Beta-Cyclodextrin (HPBCD) in artificial perilymph. Endolymphatic sac ablation caused low-frequency loss. Animals treated with HPBCD had hearing loss at all frequencies. None of these animals had loss of hair cells or synapses on auditory nerve fibers. Results: In ears with endolymphatic hydrops and those perfused with HPBCD, auditory-nerve based measurements at low frequencies showed recruitment compared to controls. Recruitment was not found at high frequencies (> 4 kHz) where hearing thresholds were normal in ears with endolymphatic hydrops and elevated in ears treated with HPBCD. Conclusions: We found compelling evidence of recruitment in auditory-nerve data. Such clear evidence has never been shown before. Our findings suggest that, in patients suspected of having endolymphatic hydrops, loudness recruitment may be a good indication that the associated low-frequency hearing loss originates from a reduction of cochlear amplification, and that measurements of recruitment could be used in differential diagnosis and treatment monitoring of Ménière’s disease.